Anesthesia Considerations for Placenta Accreta Spectrum - Warrick, Christine M.; Sutton, Caitlin D.; Farber, Michaela M.; Hess, Philip E.; Butwick, Alexander; Markley, John C. (American Journal of Perinatology, 2023)
Anesthesiologists are critical members of the multidisciplinary team managing patients with suspected placenta accreta spectrum (PAS). Preoperatively, anesthesiologists provide predelivery consultation for patients with suspected PAS where anesthetic modality and invasive monitor placement is discussed. Additionally, anesthesiologists carefully assess patient and surgical risk factors to choose an anesthetic plan and to prepare for massive intraoperative hemorrhage. Postoperatively, the obstetric anesthesiologist hold unique skills to assist with postoperative pain management for cesarean hysterectomy. We review the unique aspects of peripartum care for patients with PAS who undergo cesarean hysterectomy and explain why these responsibilities are critical for achieving successful outcomes for patients with PAS.Key Points
Keywords: anesthesia; cesarean section; hysterectomy; placenta accreta; postpartum hemorrhage